PELATIHAN METODE PENELITIAN KOMPREHENSIF BAGI KARYAWAN RUMAH SAKIT DI BAWAH YAYASAN JAMAAH HAJI KLATEN - Kuntaryanto, Oki; Jati, Agung Nugroho; Yuwono, Suhud Eko; Nursito, Sarwono; Marjukah, Anis; Hartati, Nuraeni (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
The training program on comprehensive research methods for entities under the Jamaah Haji Klaten Foundation aims to equip participants with theoretical and practical skills for conducting applied research to address institutional problems. The training materials comprise content ranging from basic to medium levels. The chosen topics mostly relate to organizational and financial matters, which are most suitable for their organizational context. Participants are obliged to conduct their own research under the supervision of instructors. Five research proposals have been submitted and are currently under supervision.. Keywords: research methods, applied research, organizational context, financial context